2022
DOI: 10.31594/commagene.1084336
|View full text |Cite
|
Sign up to set email alerts
|

Deniz Makroalgi Codium fragile (Suringar) Hariot ’in Kimyasal Bileşimi, In-Vitro Antimikrobiyal ve Antioksidan Aktivitelerinin Analizi

Abstract: Sucul alanlarda yaşayan birincil üreticiler olan deniz algleri, önemleri nedeniyle birçok araştırmaya konu olmakla birlikte ilaç, kozmetik, gıda, yakıt ve tekstil endüstrilerinde önemli rol oynayan ökaryotik ve ötrofik organizmalardır. Makroalgler, potansiyel farmakolojik kullanımları olan birkaç makro besin, mikro besin ve diğer önemli biyolojik olarak aktif bileşikler (örneğin polifenoller, enzimler ve antibiyotikler) üretmesiyle bilinmektedir. Bu araştırmada, Codium fragile (Suringar) Hariot 1889’un metanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Therefore, to estimate the protective effects of Codium fragile against PM 2.5 -induced oxidative stress, SOD activities, reduced GSH contents, and MDA levels were estimated in lung tissues ( Figure 3 ). According to a previous study, Codium fragile contains various flavonoid compounds such as naringenin, kaempferol, catechin, and epicatechin with considerable antioxidant activities [ 11 ]. Administration of these flavonoids had significant protective effects against oxidative stress-induced cytotoxicity in the systemic antioxidant system [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to estimate the protective effects of Codium fragile against PM 2.5 -induced oxidative stress, SOD activities, reduced GSH contents, and MDA levels were estimated in lung tissues ( Figure 3 ). According to a previous study, Codium fragile contains various flavonoid compounds such as naringenin, kaempferol, catechin, and epicatechin with considerable antioxidant activities [ 11 ]. Administration of these flavonoids had significant protective effects against oxidative stress-induced cytotoxicity in the systemic antioxidant system [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Codium fragile , a marine green alga belonging to the family Codiaceae , is cultivated and used for food in various countries such as the Republic of Korea, China, and Japan, and in North America [ 10 ]. Codium fragile contains various bioactive phenolic compounds, such as salicylic acid, p-coumaric acid, tamarixetin, morin, naringenin, kaempferol, and quercetin, and polysaccharides such as sulfated galactan [ 11 ]. It also has been reported that Codium fragile shows bioactive activities such as antioxidant activity, anti-diabetes, osteoarthritis inhibitory effect, hepato-protective effect, and anti-inflammatory effect [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, AECF showed protection of the HT22 and BV-2 cells by increasing the cell viability and decreasing ROS production against PM 2.5 -induced cytotoxicity [ 14 ]. It has been reported that Codium fragile contains various compounds with physiological activities such as gallic acid, 4-hydroxbenzaldehyde, 4-hydroxybenzoic acid, p -coumaric acid, and salicylic acid [ 28 ]. Gallic acid significantly improved the level of antioxidant enzymes in the body such as CAT, SOD, and glutathione peroxidase and decreased the content of MDA [ 29 ].…”
Section: Discussionmentioning
confidence: 99%